Analysis of the Impact of High-Speed Railway on County Economic Development Based on the Synthetic Control Method: The Hubei Province in China. (23rd November 2021) - Yu, Jibo; Zhou, Yuanhang; Huang, Qian; Li, Xuemei; Hou, Yiwen; Wang, Xu
Abstract : Studying the impact of the high-speed railway (HSR) on economic growth has important practical significance and can provide a theoretical basis for government investment in infrastructure. In this study, the adoption of HSR was used for natural and rigorous exploration. Based on the panel data on counties in Hubei Province of China from 2001 to 2017, a synthetic control method was used to analyse the impact of HSR on the economic growth of county-level areas with different economic bases. The results showed that HSR had different influences on the economic development of county-level cities with different economic bases in the short term. The Wuhan-Guangzhou HSR had significantly promoted the gross domestic product (GDP) growth of Chibi City with a good economic foundation. The robustness test results revealed that the promoting effect was significant at a level of 3.7%. The Hefei-Wuhan section of the Shanghai-Wuhan-Chengdu HSR had significantly inhibited the GDP growth of Hong'an County by developing on a weak economic foundation. The robustness test results revealed that the inhibitory effect was significant at the level of 2.8%. However, the Hefei-Wuhan section had a stable and promoting effect on Macheng City. Based on the abovementioned conclusions, each county-level city should focus on long-term economic development, invest in HSR construction based on local conditions instead of blind expansion, make use of HSR to vigorously develop characteristic industries, and implement talent retention and introduction policies.